FIFTEEN YEARS OF WILD TURKEY TRAPPING, BANDING, AND RECOVERY DATA IN MISSOURI - John B. Lewis (Wildlife Society Bulletin)
Abstract A trapping, banding, and recovery study of Eastern wild turkeys (Meleagris gallopavo silvestris) was conducted from 1965 through 1979 in Missouri's northern Ozarks. Spring hunting of gobblers provided recovery data for 102 known‐age, banded birds. Recovery rates were 12.3% for subadults the first season following banding; and 16.6% for adults the second year. Harvests averaged 0.4 gobbler per km2 for the 15 year period, and represented 10.6% of the average winter population. Age‐ratio data from 845 captures and recaptures, pooled for all years, suggested an average annual mortality of 52.4%. Calculation of mortality rates, using the composite dynamic method, was not possible because during 3 years of this study no individuals from the adult gobbler and adult hen segment of the population were captured.